Design analysis of a smaller-capacity straight-bladed VAWT with an asymmetric airfoil - Islam, Mazharul; Fartaj, Amir; Carriveau, Rupp (Taylor & Francis, 2011)
One of the main challenges of widespread applications of the smaller-capacity straight-bladed vertical axis wind turbine (SB-VAWT) is to design it in a cost-effective manner. The overall cost of the SB-VAWT primarily depends on the proper selection of an appropriate blade shape or airfoil to achieve desired aerodynamic performance. In this article, an attempt has been made to perform detailed design analysis with MI-VAWT1, which is a special purpose airfoil designed for smaller-capacity SB-VAWT. The present investigation has attempted to explore the viability of several innovative design concepts like alternative blade materials and incorporation of wing tip devices to reduce the induced drag of the blades of a SBVAWT. It has been found that blades manufactured from pultruded fibre reinforced plastics (FRP) are superior to conventional aluminium. Also, the aerodynamic performance of MI-VAWT1 is better than that of conventionally used NACA 0015. © 2011 Taylor & Francis.